1990
DOI: 10.1021/j100376a032
|View full text |Cite
|
Sign up to set email alerts
|

Polarity of AOT micellar interfaces: use of the preferential solvation concepts in the evaluation of the effective dielectric constants

Abstract: Fluorescence lifetimes (rF) of 2-[p-(dimethylamino)phenyl]-3,3-dimethyl-3//-indole (1) have been extensively studied in a two-component mixture of p-dioxane/water and also in a three-component mixture of n-heptane/AOT (sodium bis(2-ethylhexyl) sulfosuccinate)/water. We have applied the concept of "dielectric enrichment" to solute/mixed solvents systems in order to evaluate the effective dielectric constants at the AOT interfaces in «-heptane. We have shown that the effective dielectric constant (D) at the inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
73
0

Year Published

1992
1992
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 129 publications
(83 citation statements)
references
References 0 publications
10
73
0
Order By: Relevance
“…Both experimental [119][120][121][122] and MD simulations [123][124][125][126] have revealed that water confined in systems such as reverse micelles and biological pores possesses a decreased polarity and rate of relaxation, and an increased degree of spatial and orientational order, when compared to bulk water. As such, assumptions of a constant dielectric constant for the water in the pore of a PEM (either that of bulk water or some other values) is clearly incorrect.…”
Section: Dielectric Saturationmentioning
confidence: 99%
“…Both experimental [119][120][121][122] and MD simulations [123][124][125][126] have revealed that water confined in systems such as reverse micelles and biological pores possesses a decreased polarity and rate of relaxation, and an increased degree of spatial and orientational order, when compared to bulk water. As such, assumptions of a constant dielectric constant for the water in the pore of a PEM (either that of bulk water or some other values) is clearly incorrect.…”
Section: Dielectric Saturationmentioning
confidence: 99%
“…Such dramatic differences of λ em max and φ f of TNS in the water pool of the microemulsions compared to ordinary bulk water indicates that the microenvironment of the TNS in the water pool is significantly different from bulk water. On further addition of water as the water pool swells in size and its polarity increases [26][27][28] the φ f decreases gradually to 0.063 at w 0 =32 and λ em max exhibits a red shift to 450 nm. However it should be noted that even at w 0 =32 emission properties of TNS is markedly different from those in bulk water.…”
Section: Steady State Spectramentioning
confidence: 99%
“…Firstly, the dielectric relaxation time (τ D ) indicates a bimodal behavior with one component of 10 ps which is similar to ordinary water and another of 10 ns which is thousand times slower compared to bulk water. [11][12][13][14] Secondly, comparing the position of the steady state absorption or emission maxima of many probe molecules in the water pools with those in different solvents [26][27][28] (or comparing present data on TNS with ref. 19) the static dielectric constant (ε 0 ) of the water pool of the microemulsions seems to be close to that of alcohol (i.e.…”
Section: Time Resolved Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…From the NMR (self-)diffusion measurements it is concluded that bicontinuous structures exist in microemulsions of the surfactant p(7-4-C 14) in benzene and water. On increasing the concentration of p (7-4-C,,), the interactions between microemulsion droplets in benzene change from strongly interacting droplets to non-interacting, hard spheres.…”
Section: Discussionmentioning
confidence: 99%